1947
DOI: 10.1002/jez.1401060307
|View full text |Cite
|
Sign up to set email alerts
|

The role of androgen in declining regenerative capacity during morphogenesis of the Platypoecilus maculatus gonopodium

Abstract: It has been shown previously (Grobstein, '47) that cluring morphogenesis of the Platypoecilus maculatus gonopodium regenerative capacity sharply declines. Whereas the immature anal fin or the anal fin of the adult female regenerates completely following amputation, the adult male aual fin, modified under the iilfiuence of androgen into a copulatory organ, regenerates abortively and atypically. It is the purpose of the present paper to describe the results of experiments to elucidate the role of androgen in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1948
1948
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Pituitary growth hormone of mammalian origin is able to promote the growth offish (Swift, 1954). The relation between morphogenesis under the influence of gonadal hormones and loss of regenerative power has special interest in gerontology. Grobstein (1947) found that when the gonopodium of poeciliid fish differentiates, under the influence of androgens, regenerative power is lost: he stresses the analogy between this process and the loss of regenerative capacity in the developing anuran limb. Such a change need not depend upon irreversible loss of cellular capacity to grow-this does The Mechanisms of Senescence not appear to be the case in amphibian limbs (Borssuk, 1935;Polezaiev and Ginsburg, 1939) but the physiological loss of repair-power may be as complete, so far as the intact animal is concerned, as is the loss of moulting-power in Rhodnius once the evocator is lost.…”
Section: -2-3 Hormonal Regulation Of Growth In Vertebratesmentioning
confidence: 99%
“…Pituitary growth hormone of mammalian origin is able to promote the growth offish (Swift, 1954). The relation between morphogenesis under the influence of gonadal hormones and loss of regenerative power has special interest in gerontology. Grobstein (1947) found that when the gonopodium of poeciliid fish differentiates, under the influence of androgens, regenerative power is lost: he stresses the analogy between this process and the loss of regenerative capacity in the developing anuran limb. Such a change need not depend upon irreversible loss of cellular capacity to grow-this does The Mechanisms of Senescence not appear to be the case in amphibian limbs (Borssuk, 1935;Polezaiev and Ginsburg, 1939) but the physiological loss of repair-power may be as complete, so far as the intact animal is concerned, as is the loss of moulting-power in Rhodnius once the evocator is lost.…”
Section: -2-3 Hormonal Regulation Of Growth In Vertebratesmentioning
confidence: 99%
“…Immature males were castrated according to the method of Grobstein (1947). After the operation the fish are placed in conditioned aquarium water to which commercial sea salts have been added to make a 0-9% salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…Examples also exist demonstrating that transitions in tissue regenerative capacity during development are associated with a peak of hormone production or prolonged elevation of hormone levels in animals (Alberch et al, 1986;Hirose et al, 2019;Larras-Regard et al, 1981). The inability of tissue to regenerate following hormone exposure is not only limited to tissue that has undergone an injury; tissue exposed to high levels of hormones during development may also lack the ability to regenerate later in life (Grobstein, 1947), suggesting that transient exposure to hormone signals can sculpt future regenerative responses to injury.…”
Section: Circulating Hormones Regulate Tissue Regenerationmentioning
confidence: 99%